Fracture Healing in Elderly Mice and the Effect of an Additional Severe Blood Loss: A Radiographic and Biomechanical Murine Study - Katrin Bundkirchen; Weikang Ye; Aleksander J. Nowak; Stefan Lienenklaus; Bastian Welke; Borna Relja; Claudia Neunaber (Bioengineering, 2023)
Femoral fractures and severe bleeding frequently occur in old patients showing a delayed healing. As there are no studies investigating the combined effect of high age and severe blood loss on fracture healing, this was examined radiographically and biomechanically in this study. Therefore, young and old male mice were randomly assigned to three operation groups. In the fracture group (Fx), external fixator and osteotomy were applied to the femur. The combined trauma group (THFx) additionally received a pressure-controlled hemorrhage. Sham animals were only implanted with arterial catheter and external fixator. Sacrifice was performed after three weeks and bone healing was evaluated radiologically via µCT, as well as biomechanically using a three-point bending test. A decreased share of callus/total bone volume was observed in old mice with blood loss compared to old Fx. Hemorrhagic shock also reduced the trabecular number in old mice compared to Fx and young THFx. Moreover, a lower elastic limit in old Sham mice without fracture was revealed. Fracture combined with a high loss of blood further reduced the elastic limit in old mice compared to isolated Fx in old animals. In conclusion, this study showed that severe blood loss has a higher negative effect in old mice compared to young ones.